The immunosuppressive tuberculosis-associated microenvironment inhibits viral replication and promotes HIV-1 latency in CD4+ T cells - Cronin, Samantha (2024)
Mycobacterium tuberculosis (Mtb), the causative agent of tuberculosis (TB), is the most common coinfection among people living with HIV-1. This coinfection is associated with accelerated HIV-1 disease progression and reduced survival. However, the impact of the HIV-1/TB coinfection on HIV-1 replication and latency in CD4+ T cells remains poorly studied. Using the acellular fraction of tuberculous pleural effusion (TB-PE), we investigated whether viral replication and HIV-1 latency in CD4+ T cells are affected by a TB-associated microenvironment. Our results revealed that TB-PE impaired T cell receptor-dependent cell activation and decreased HIV-1 replication in CD4+ T cells. Moreover, this immunosuppressive TB microenvironment promoted viral latency and inhibited HIV-1 reactivation. This study indicates that the TB-induced immune response may contribute to the persistence of the viral reservoir by silencing HIV-1 expression, allowing the virus to persist undetected by the immune system, and increasing the size of the latent HIV-1 reservoir.